Penerapan Aplikasi SLiMS 8 Akasia Dalam Pengolahan Bahan Pustaka Di Perpustakaan Perguruan Tinggi - Nurdiansyah, Aulia (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2022)
Globalization Era 4.0 Libraries based on information technology are developing very rapidly, where one of the objectives of the development is to make it easier for librarians and users. Utilization of Open source software Senayan Library Management System as a basis for developing a Library Information System. The purpose of this study is to determine the role and influence of the SLiMS 8 Akasia application in processing library materials in universities. The method used in this study is the research conducted by the researcher is a type of development research or Research and Development (R&D). The results of this study are that the use of SLiMS 8 Akasia can make it easier for all parties, both librarians as library managers, and students as users of library materials in this case the modules